“Análisis de la coordinación de la protección 67 en las líneas del anillo de 230 kv del sistema nacional ecuatoriano en el escenario de máxima lluvia.” - Romero Toro, Eduardo Xavier (2024)
In this research project, the analysis of the operation of the directional (67) and instantaneous (50) overcurrent relays in the 230 kV ring lines of the Ecuadorian National System under the maximum rainfall scenario was carried out through the use of DigSilent Power Factory software. The project started with creating Boundaries and the equivalent of a type network in the system to reduce and simplify the network, thus obtaining an effective and efficient analysis. Then, the power flow calculations in the lines, execution of short circuits in the line terminals, and sizing of CT and PT were carried out. For the calibrations of the overcurrent protections, the selectivity criterion was considered for relay 50 and the quadrature polarization method for relay 67. Likewise, the relays were incorporated into the simulation, and three-phase faults were performed at a 50% distance in each of the lines of the system ring. On the other hand, the simulation was performed in counterclockwise and clockwise directions for the analysis due to the directionality of relay 67. Finally, it was possible to observe, through the operating curves, how the overcurrent protection acts effectively in case of a fault in the protected element with a more significant time variation than the other backup relays in a clockwise and counterclockwise direction, achieving adequate coordination and an optimal configuration for three-phase faults.